The discovery of IDX21437: Design, synthesis and antiviral evaluation of 2′-α-chloro-2′-β-C-methyl branched uridine pronucleotides as potent liver-targeted HCV polymerase inhibitors. Issue 18 (15th September 2017) - Alexandre, François-René; Badaroux, Eric; Bilello, John P.; Bot, Stéphanie; Bouisset, Tony; Brandt, Guillaume; Cappelle, Sylvie; Chapron, Christopher; Chaves, Dominique; Convard, Thierry; Counor, Clément; Da Costa, Daniel; et al.
Graphical abstract: Abstract: Herein we describe the discovery of IDX2143735b, a novel RP d -aminoacid-based phosphoramidate prodrug of 2′-α-chloro-2′-β- C -methyluridine monophosphate. Its corresponding triphosphate6 is a potent inhibitor of the HCV NS5B RNA-dependent RNA polymerase (RdRp). Despite showing very weak activity in the in vitro Huh-7 cell based HCV replicon assay, 35b demonstrated high levels of active triphosphate6 in mouse liver and human hepatocytes. A biochemical study revealed that the metabolism of35b was mainly attributed to carboxyesterase 1 (CES1), an enzyme which is underexpressed in HCV Huh-7-derived replicon cells. Furthermore, due to its metabolic activation, 35b was efficiently processed in liver cells compared to other cell types, including human cardiomyocytes. The selected RP diastereoisomeric configuration of35b was assigned by X-ray structural determination.35b is currently in Phase II clinical trials for the treatment of HCV infection.